Analysis Students’ Speaking Skill Based on Local Material at First Semester in English Department of Unswagati - Afiah, Devi Siti Sihatul (Universitas Swadaya Gunung Jati, 2016)
The goals of this research were: (1) To analyze the students’ mistakes in speaking skill; (2) To find out the difficulties of local topics in speaking. This research used the descrivtif qualitative method. The writer described and analyzed the students’ errors in speaking skill and the difficulties used the local materials. The research was carried out at the first year students of english department in 2015/2016 academic year. it was strated from Februari to May 2016. The population was the first semester students of english department in academic year of 2015/2016. The number of population was 27 students. The results of this research were: (1) lots of students were able to speak well and few of them were still lack (2) Some of students felt difficult to use some words of local tpoics in speaking